Implementation of Number Head Together (NHT) Type of Cooperative Learning Model in IPS Class V Students at SDI Bukkangraki Bajeng District, Gowa Regency: Study of Achievement Motivation and Student Learning Outcome - Muliadi Muliadi; Rosleny B; Jamaluddin Arifin (Edumaspul: Jurnal Pendidikan, 2023)
The research objectives were to find out 1) the application of the Number Head Together (NHT) Cooperative learning model to Grade V students at SDI Bukkangraki, Bajeng District, Gowa Regency; 2) Achievement Motivation of Class V Students in the Application of the Number Head Together (NHT) Cooperative Learning Model at SDI Bukkangraki, Bajeng District, Gowa Regency; 3) Learning Outcomes of Class V Students in Number Head Together (NHT) Type Cooperative Learning at SDI Bukkangraki, Bajeng District, Gowa Regency. This type of research is qualitative. Data collection instruments used were observation, interviews, and documentation. Data collection techniques are observation, interviews, and documentation studies. Data analysis used is data reduction, data presentation, and data verification or conclusion. The research results obtained are the application of the Number Head Together (NHT) Cooperative learning model directing students to work together in groups so that they can motivate achievement in learning success, seen from the enthusiasm and activeness of students in the learning process and being able to understand and do assignments in a timely manner with friends groups, making students interact with other students in class, while learning achievement can be assessed from three domains, namely affective, cognitive, psychomotor so that the achievement of student learning outcomes is maximized.